Restoring a critically endangered grassland orchid by co-planting to improve pollination and selecting sites based on pollinator availability - Reiter, Noushka; Dimon, Richard; Bohman, Björn; Batley, Michael; McLachlan, Alex; Woodward, John; Phillips, Ryan D. (Frontiers in Plant Science, 2025)
In many geographic regions grasslands have been heavily cleared and degraded, which represents a challenge for translocating threatened flora back into these landscapes. As most plant species require animals for pollination, pollinators are potentially a key limitation for re-establishing populations. For the Critically Endangered orchid Diuris fragrantissima, we identify the pollinator(s), survey for pollinators at candidate translocation sites, test if remnant size affects bee species richness, and test if pollination rates can be enhanced through co-planting with rewarding plant species. We found that D. fragrantissima is visited by ten species of bee but is only effectively pollinated by two native species, Lipotriches (Austronomia) sp. (Halictidae) and Lasioglossum (Chilalictus) orbatum (Halictidae), and the introduced honeybee Apis mellifera (Apidae). Interestingly, A. mellifera was responsible for the greatest number of pollinia removals and depositions. Pollinators of D. fragrantissima were not detected at some candidate translocation sites, with bee species richness and overall abundance significantly increasing with grassland remnant size. The pollination of D. fragrantissima was significantly enhanced through the presence of Wahlenbergia stricta (Campanulaceae) within 30 cm of plants, but not Arthropodium strictum (Asparagaceae) or Dianella reflexa (Asphodelaceae). We recommend that prior to conservation translocations of Diuris that pollinator surveys are undertaken, with preference given to larger grassland remnants. Apis mellifera may serve to buffer D. fragrantissima against loss of native pollinators from remnant grassland but could have adverse effects on other native species. We show that co-planting with rewarding species may be an effective approach for improving pollination success of threatened orchids.